Practice of profit equalization reserve and investment risk reserve by Islamic banks - Htay, Sheila Nu Nu; Syed, Ahmed Salman (K.A.J Printing Islamabad, Pakistan, 2013)
Stability of banking system is backbone of any country’s economy. Conventional banking is a prominent banking system and it is well established in both Muslim and non-Muslim countries. Recently, Muslim scholars have suggested Islamic banking which has been widely practiced all over the world. All the Islamic banks except in Sudan are operating in the environment whereby the conventional banking has been dominating since a few decades. Although a few countries like Malaysia are facilitating Islamic banks, they are still influenced by the dominated conventional banking. In some scenarios, there are no rules and regulation governing Islamic banks. Islamic institutions such as AAOIFI and IFSB and regulatory bodies like Bank Negara Malaysia come out with some guidelines to ensure that Islamic banks are competitive with conventional banks and the former ones are able to attract the investment account holders (IAHs) as well as to stabilize the whole country banking system. Among the guidelines, the most important guideline is related to the practice of profit equalization reserve and investment risk reserve. Thus, the aim of this paper is to highlight the important role of these reserves and the recommendations provided by Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), Islamic Financial Services Board (IFSB) and Bank Negara Malaysia (BNM) on their practices. The guidelines cover how much percentage of profit can be allocated for reserves and the transparent disclosure on this matter. Finally, the Shari’ah resolution by BNM is highlighted. It is expected that this paper will widen the knowledge of all interested parties on Islamic banking practices, especially on these reserves.